NDM-1 encoded by a pNDM-BJ01-like plasmid p3SP-NDM in clinical Enterobacter aerogenes - Chen, Zhenhong; Li, Hongxia; Feng, Jiao; Li, Yuxue; Chen, Xin; Guo, Xuemin; Chen, Weijun; Wang, Li; Lin, Lei; Yang, Huiying; Yang, Wenhui; Wang, Jie; et al. (Frontiers in Microbiology, 2015)
A carbapenem-nonsusceptible Enterobacter aerogenes strain named 3-SP was isolated from a human case of pneumonia in a Chinese teaching hospital. NDM-1 carbapenemase is produced by a pNDM-BJ01-like conjugative plasmid designated p3SP-NDM to account for carbapenem resistance of 3-SP. p3SP-NDM was fully sequenced and compared with all publically available pNDM-BJ01-like plasmids. The genetic differences between p3SP-NDM and pNDM-BJ01 include only 18 single nucleotide polymorphisms, a 1 bp deletion and a 706 bp deletion. p3SP-NDM and pNDM-BJ01 harbor an identical Tn125 element organized as ISAba125, blaNDM-1, bleMBL, ∆trpF, dsbC, cutA, ∆groES, groEL, ISCR27 and ISAba125. The blaNDM-1 surrounding regions in these pNDM-BJ01-like plasmids have a conserved linear organization ISAba14-aphA6-Tn125-unknown IS, with considerable genetic differences identified within or immediately downstream of Tn125. All reported pNDM-BJ01-like plasmids are exclusively found in Acinetobacter, whereas this is the first report of identification of a pNDM-BJ01-like plasmid in Enterobacteriaceae.